The development of feeding behavior in wild chimpanzees (Pan troglodytes schweinfurthii). Issue 1 (26th September 2017) - Bray, Joel; Emery Thompson, Melissa; Muller, Martin N.; Wrangham, Richard W.; Machanda, Zarin P.
Abstract: Objectives: Primates have an extended period of juvenility before adulthood. Although dietary complexity plays a prominent role in hypotheses regarding the evolution of extended juvenility, the development of feeding behavior is still poorly understood. Indeed, few studies have investigated the timing and nature of feeding transitions in apes, including chimpanzees. We describe general patterns of feeding development in wild chimpanzees and evaluate predictions of the needing‐to‐learn hypothesis. Materials and Methods: We analyzed 4 years of behavioral data (2010–2013) from 26 immature chimpanzees and 31 adult chimpanzees of the Kanyawara community in Kibale National Park, Uganda. Specifically, we examined milestones of nutritional independence (first consumption of solid food and cessation of suckling) as well as developmental changes in feeding time, diet composition, diet breadth, and ingestion rates. Results: Chimpanzees first fed on solid food at 5.1 months and, on average, suckled until 4.8 years. Daily feeding time of immature individuals reached adult levels between 4 and 6 years, while diet composition showed minor changes with age. By juvenility (5–10 years), individuals had a complete adult diet breadth. Ingestion rates for five ripe fruit species remained below adult levels until juvenility but continued to show absolute increases into adolescence. Discussion: Chimpanzees acquired adult‐like patterns on all feeding measures by infancy or juvenility. These data are inconsistent with the needing‐to‐learn hypothesis; moreover, where delays exist, alternatives hypotheses make similar predictions but implicate physical constraints rather than learning as causal factors. We outline predictions for how future studies might distinguish between hypotheses for the evolution of extended juvenility.